32-and 34-Membered Macrocyclic Trinuclear Nickel(II) Complexes - Rai, H.C.; Kumar, A.; Kumari, Veena (Asian Journal of Chemistry, 2010)
An interesting group of 32- and 34-membered macrocyclic trinuclear nickel(II) complexes have been isolated by synergic template condensation of bis-(dihydrazone) nickel(II) bromide complexes with a suitable dialdehyde nickel(II) bromide complex in molar ratio 1 : 2.